2016
DOI: 10.1111/tmi.12684
|View full text |Cite
|
Sign up to set email alerts
|

What factors affect patient access and engagement with clubfoot treatment in low‐ and middle‐income countries? Meta‐synthesis of existing qualitative studies using a social ecological model

Abstract: Abstractobjectives To conduct a systematic synthesis of previous research to identify factors that affect treatment-seeking for clubfoot and community-level interventions to improve engagement in low-and middle-income counties.methods A search of five databases was conducted, and articles screened using six criteria. Quality was appraised using the Critical Appraisal Skills Programme checklist. Eleven studies were identified for inclusion. Analysis was informed by a social ecological model, which specifies fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 24 publications
2
22
0
1
Order By: Relevance
“…Focusing specifically on patient poverty as a main barrier to Treat All implementation, the study revealed that patients’ lack of capacity to pay for baseline investigation or transport services to clinics limited their ability to access treatment services. The results re-affirms the concept of a wider set of determinants for health and the important effect of socioeconomic factors in determining the health of individuals [33-35].…”
Section: Discussionsupporting
confidence: 72%
“…Focusing specifically on patient poverty as a main barrier to Treat All implementation, the study revealed that patients’ lack of capacity to pay for baseline investigation or transport services to clinics limited their ability to access treatment services. The results re-affirms the concept of a wider set of determinants for health and the important effect of socioeconomic factors in determining the health of individuals [33-35].…”
Section: Discussionsupporting
confidence: 72%
“…A narrative synthesis was conducted in four stages: identifying studies for inclusion, appraising quality, data extraction and synthesis and reporting findings. Methods correspond to our previous meta-synthesis exploring treatment-seeking behaviour for clubfoot [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
“…Articles were then categorised into three groups. These were: ‘fully addresses CASP items’, ‘mainly addresses CASP items’ or ‘partially addresses CASP items’ [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations